Монгол хэлний үйлээс нэр үг бүтээх “-ц” дагаврын утгын асуудалд: Semantic aspects of the Mongolian verb-forming suffix “-ts” - Б., Мөнгөнцэцэг (Mongolian Studies, 2023)
Considering the characteristic according to meaning of Mongolian suffix “-ц” forms the noun from the verb, the words can be related with the vocabulary and meaning of the words’ meaning. According to the factual relation, in most cases when using this suffix for actions in active form, it expresses the things’ relation and the place which actions would be happened, object of the actions, subject of the actions, the meaning which has been created by the actions revealed fewer. While according to the abstract or sign relations, it expresses the mood or measurement in meaning if not in objective mood.